ANALISIS PENERAPAN AKUNTANSI LINGKUNGAN PADA RUMAH SAKIT PELAMONIA MAKASSAR - Chyntiani, Shinta (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2025)
This research aims to find out how environmental accounting is implemented in efforts to prevent waste at Pelamonia Hospital Makassar. The data collection methods and techniques used in this research were descriptive qualitative methods and direct interviews with K3RS departments related to environmental management costs. The data used comes from documentation or internal hospital data. From the research results, it was found that Pelamonia Makassar Hospital has managed its waste well and has carried out accounting treatment stages for environmental management costs consisting of liquid and solid waste costs, water costs, fuel, electricity, space and building sanitation, air quality monitoring. , insect control and WWTP costs. With this research, it is hoped that Pelamonia Makassar Hospital will implement environmental accounting better